Factors underlying the vocational teachers' attitudes towards the integration of computer in teaching. - Bakar, Ab Rahim; Mohamed, Shamsiah (2007)
The main aim of the papers was to discuss factors underlying the vocational teachers' attitude towards the integration of computers in teaching vocational subjects. The study revealed that vocational teacher have positive attitudes towards the integration of computer tehnology in teaching. Teachers' attitudes were further classified into four factors using analysis procedure. The four factors were confidence, educational value, apprehension, and liking towards computer. They believed that the integration of computers is beneficial, but they were not quite confiednt to integrate computer technology in teaching. They were not apprehensive with the idea of computer integration in teaching and they like to integrate computer in teaching. Although teachers do not have the confidence, the study shows that teacher are not that apprehensive in the integration of computer in teaching and they like the idea of integration computer in teaching. The total amount of of variance uniquely explained by the four underlying constructs of teachers' attitudes towards the integration of computers in teaching vocational subejcts was 53.82%.